ANALISIS PENERAPAN ETIKA BISNIS TERHADAP STAFF PURCHASING DALAM PERUSAHAAN (Studi Kasus PT. Sentratek Adiprestasi) - Maria Christisia (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
In the contemporary competitive landscape of diverse business enterprises, the exigency for excellence has intensified, prompting a strategic emphasis on business ethics as a linchpin for fortifying corporate integrity and elevating service quality. This commitment to ethical principles serves as a catalyst for cultivating robust internal relationships, thereby engendering heightened levels of customer satisfaction and fostering superior consumer experiences. In the pursuit of customer contentment, companies prioritize the delivery of high-caliber products. The procurement team, functioning as a pivotal nexus in material sourcing, actively engages with suppliers through the solicitation of quotations, thereby securing agreements on advantageous pricing and uncompromising product quality. This research endeavors to comprehensively scrutinize and explicate the nuanced application of business ethics within the purview of the purchasing staff at PT. Sentratek Adiprestasi. The overarching objective is to propagate and institutionalize a culture of ethical conduct, thereby augmenting the perceived corporate value vis-à-vis both clientele and suppliers and reinforcing the company's competitive standing within the marketplace.